(untitled) - Dr. Harpreet Kaur Arora (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Premchand the emperor of novels used literature for the important purpose of arousing public awareness about national and social issues. He was a great social reformer who wrote about the issues faced by the urban middle class including exploitation, prostitution, widowhood and the freedom movement and thus worked to generate patriotism and nationalistic sentiments in the general populace.In Karmabhoomi (arena of action 1932) the focus is on the nationalist struggle of the country, it is a beautiful fusion of vision and reality based on human emotions. The novel gives us a glimpse into the freedom struggle led under the leadership of Mahatma Gandhi.